Jewish Perversion as Strategy of Domination: The anti-Semitic Subtext of Anti-gender Discourse. Issue 3 (August 2022) - Graff, Agnieszka
This article demonstrates how anti-gender discourse – originating in the Vatican and spreading through ultra-conservative networks such as the World Congress of Families – draws on traditions of conspiratorial anti-Semitism. The repressed link takes two forms: displacement (Judaization of sexual minorities) and attribution of blame (Jews having invented 'gender' to destroy Christianity). The first section outlines the structural and historical kinship between the two discourses. Anti-gender discourse continues the 19th-century strand of European anti-Semitism that operates as a cultural code for anti-modernism, reproducing its conspiratorial and polarizing structure and repeating the stereotypes of gendered anti-Semitism. Part two examines an example of disguised anti-Semitic subtext: Gabriele Kuby's Global Sexual Revolution (2015), a central text of anti-genderism, is shown to draw on the writings of E. Michael Jones, a 'Radical Catholic Traditionalist'. Jones claims that Jews have been plotting for centuries to destroy Western Civilization and enjoys a certain popularity with the Polish right. The final section reflects on the elusiveness of the anti-Semitic subtext and its dependence on cultural context. The displacement of Jews by 'gender' facilitates the mainstreaming of right-wing extremism and helps legitimize radical-right groups as political players.